Asia and the Historical Imagination (Springer Singapore, 2018)
This collection explores the interpretation of historical fiction through fictional representations of the past in an Asian context. Emphasising the significance of region and locality, it explores local networks of political and cultural exchanges at the heart of an Asian polity. The book considers how imagined pasts converge and diverge in developed and developing nations, and examines the limitations of representation at a time when theories of world literature are shaping the way we interpret global histories and cultures. The collection calls attention to the importance of acknowledging local tensions-both within the historical and cultural make-up of a country, and within the Asian continent-in the interpretation of historical fiction. It emphasizes a broad-spectrum view that privileges the shared historical experiences of a group of countries in close proximity, and it also responds to the paradigm shift in Asian Studies. Discussing how local conditions shape and create expectations of how we read historical fiction and working with the theme of fictionality and locality, the volume provides an alternative framework for the study of world literature.